Sistem Informasi Penilaian Akademik Siswa Berbasis Web (Studi Kasus: SMA Al-Kautsar) - Riski Husniawan; Khaerul Ma’mur (CV. Shofanah Media Berkah, 2023)
Report cards are reports that are processed by subject teachers to determine the progress of student learning outcomes during a certain period. The management of student report cards is a series of work that requires accuracy because in the report cards there will be a lot of data to be managed. In this case, the management of student report cards at Al-Kautsar High School which has been running until now, where each teacher will manage the value of the student report cards they have by exchanging the data that has been inputted into the new data to be managed. Furthermore, the data that has been inputted by the teacher will be submitted to the staff (administration) section. Furthermore, the staff will re-manage the student report card score data received from the teacher to become the student report card value that will be printed, so that the process of making student report cards will have to work twice because between the teacher and staff the data does not match. The purpose of this research is to be able to produce applications to manage student academic assessments that can be accessed through the website and in the application will manage a lot of data, such as data on student report cards, students, teachers, classes, student classes, lessons and others. In this study, the author uses the waterfall method, where the waterfall method can describe a systematic and sequential approach to software development. This study uses the Black Box as a test carried out on the student grade report card management application, where the results of the Black Box testing on the application can run well according to its function and can be implemented at Al-Kautsar High School.